COMMUNITY PERCEPTION OF CORAL REEF DAMAGE CAUSED BY THE IMPACT OF MAINLAND COASTAL DEVELOPMENT ACTIVITIES (International Conference on Social and Islamic Studies, 2021)
The main land coastal development activities (Makassar City and its surroundings) have direct and indirect impacts on the community and the environment, especially fishermen who catch fish on the coral reefs of the Spermonde Archipelago. These activities include sea sand extraction and beach reclamation for the construction of ports and waterfront cities. The perceived impact consists of positive and negative values. This study aims to analyze the community perception of coral reef damage caused by the impact of mainland coastal development activities in Makassar City and its surroundings. This research was conducted from October to November 2021 on Barrang Caddi Island, Badi Island and Bontosua Island, Spermonde Archipelago. This research is classified as ex post facto with descriptive quantitative survey method. Respondents in this study as many as 200 people who make a living as fishermen. Determination of informants is done by stratified random sampling method. The measurement of the degree of perception is measured by the Likert scale method. The results of the study indicate that the positive value impacts are to provide security from the crime of illegal fishing, and the community gets a side job, namely the activity of rehabilitating coral reefs. The negative value impacts are the disruption of local wisdom, the increase in environmental pollution, the decrease in the number of fish catches, as well as higher fishing operational costs incurred. To manage public perception, it is necessary to manage the impact of development and community empowerment in a sustainable manner.